Yolo-tiny-MSC: A tiny neural network for object detection. Issue 1 (April 2021) - Li, Dongsheng; Zhang, Yujie; Xiang, Junping; Li, Jianfei; Zou, Yu
Abstract: Object detection is an important and active area of computer vision. However, the expensive computational cost and memory requirement are big challenges for deploying object detection networks in resource constraints embedded devices. To address this problem, we designed the multi-stage cascade module to reduce the computational cost of object detection networks. The proposed structure is used to build a compact and efficient object detection neural network. Experiments show that our multi-stage cascade module could significantly reduce the computational and parameter budgets meanwhile achieve outstanding object detection accuracy.